Exploring the role of religious motivation towards tourist satisfaction: a proposed Islamic tourism model from a Malaysian perspective - Haque, A. K. M. Ahasanul; Abdul Razak, Dzuljastri; Momen, Abdul; Anwar, Asmalina; Hashim, Nurhazirah (2014)
The purpose of the study is to identify factors inﬂuencing tourist satisfaction of Islamic tour destination under the Islamic tourism concept. The study is conceptual in nature.It develops a Tourist Satisfaction Model derived from the comprehensive literature review and prior empirical findings where the relationships among Religious Motivation, Destination Selection, Destination Image, Perceived Value, Service Quality and Tourist Satisfaction are depicted. The theoretical supports of this research provides justifiable evidence that the proposed Tourist Satisfaction Model is acceptable. The research indicates that Malaysia as an Islamic tourism Destination haswide acceptance to the Muslim tourists all around the world. A further study can be addressed to test the model empirically and conﬁgure relative importance of the causing factors behind the tourist satisfaction. The proposed model may give the practitioners a way to develop their destination as an Islamic tourism center while academician can ﬁnd a comprehensive model to test for the specific destination.